THE EFFECTS OF INTRAVENOUS FLUIDS TEMPERATURE ON PERIOPERATIVE HEMODYNAMIC SITUATION, POST-OPERATIVE SHIVERING, AND RECOVERY IN ORTHOPAEDIC SURGERY - Hasankhani, H; Mohammadi, E; Moazzami, F; Mokhtari, M; Naghgizadh, M (Operating Room Nurses Association of Canada Journal, 2007)
Background: Perioperative hypothermia is physiologically stressful because it elevates blood pressure, heart rate and plasma catecholamine concentration that may increase the risk of cardiac complications, bleeding, wound infection, and post-anaesthesia care unit stay. This study was designed to evaluate the effects of warming intravenous fluids on perioperative hemodynamic situation, post-operative shivering and recovery in orthopaedic surgery patients. Methods: Perioperative pulse rate, blood pressure, intraoperative esophageal and skin temperature were measured in sixty patients undergoing orthopaedic surgery that were randomly divided into two groups according to intraoperative IV fluids management. In 30 patients (hypothermia group) all IV fluids infused were at room temperature. In the other 30 patients (normothermia group) all IV fluids were warmed using a dry IV fluid warmer. Results: The core and skin temperatures of the hypothermia and normothermia groups decreased significantly between the induction of anesthesia and the end of surgery, but the drop was greater in the hypothermia group (P<0.005). Postoperative mean arterial blood pressure (non-invasive) increased significantly more in the hypothermia group versus normothermia group (p<0.005). Shivering was observed in 21 of 30 in the hypothermia group and 11 of 30 in the normothermia group (p<0.005) and recovery time was significantly lower in the normothermia group (36±5 vs. 26±3 min, p< 0.005). Conclusion: Intraoperative IV fluid warming reduces perioperative changes to the hemodynamic situation, post-operative shivering, and recovery time. Key words: Intravenous fluids temperature, hemodynamic situation, shivering, recovery, and orthopaedic surgery.